Effect of subsidies on healthful consumption: a protocol for a systematic review update. Issue 8 (20th August 2020) - Pearson, Fiona; Huangfu, Peijue; Abu-Hijleh, Farah M; Awad, Susanne F; Abu-Raddad, Laith J; Critchley, Julia A
Abstract : Introduction: The prevalence of diet-related non-communicable diseases (NCDs) are rapidly increasing in most parts of the world. In order to ameliorate the related public health burden, evidence-informed policies to improve diet need to be implemented. Financial subsidies that promote healthful consumption patterns have the potential to reduce NCD risk and may also reduce inequality if targeted at those of low socio-economic position. This protocol is for an updated systematic review of such evidence. Methods and analysis: A systematic search strategy will be used to identify publications on fiscal intervention studies indexed in Embase, CINAHL, Web of Science, EconLit and PubMed in between January 2013 to February 2019. Two reviewers will independently sift identified citations using prespecified inclusion and exclusion criteria to inform full-text review. The outcomes of interest are: consumption patterns (% change in targeted items and in overall dietary patterns), purchasing patterns (% change) or body mass index. Pretested data capture forms will be used for double data extraction. Any inconsistencies in citation sifting or data extraction will be resolved by a third investigator and study authors will be contacted if needed. Systematic searches will be supplemented by reference checking of key articles. Study quality will be assessed and a narrative summary of findings will be produced. Meta-analyses and exploration of heterogeneity will be completed if appropriate. Ethics and dissemination: The review aims to strengthen findings of the primary studies it incorporates. It will synthesise existing published aggregated patient data and only present further aggregate data. Given this, no concerns are held relating to confidentiality and informed consent due to re-use of patient data. If publications or data with ethical concerns are identified, they will be excluded from the review. Results of the systematic review will be published in full and authors will engage directly with research audiences and key stakeholders to share findings. PROSPERO registration number: CRD42019125013